Closing the gap: the potential of Christian Health Associations in expanding access to family planning - Lauren VanEnk; Ronald Kasyaba; Prince Bosco Kanani; Tonny Tumwesigye; Jeannette Cachan (Health for All Nations, 2017)
Recognizing the health impact of timing and spacing pregnancies, the Sustainable Development Goals call for increased access to family planning globally. While faith-based organizations in Africa provide a significant proportion of health services, family planning service delivery has been limited. This evaluation seeks to assess the effectiveness of implementing a systems approach in strengthening the capacity of Christian Health Associations to provide family planning and increase uptake in their communities.From January 2014 to September 2015, the capacity of three Christian Health Associations in East Africa-Caritas Rwanda, Uganda Catholic Medical Bureau, and Uganda Protestant Medical Bureau-was strengthened with the aims of improving access to women with unmet need and harmonizing faith-based service delivery contributions with their national family planning programs. The key components of this systems approach to family planning included training, supervision, commodity availability, family planning promotion, data collection, and creating a supportive environment. Community-based provision of family planning, including fertility awareness methods, was introduced across intervention sites for the first time. Five hundred forty-seven facility- and community-based providers were trained in family planning, and 393,964 people were reached with family planning information. Uptake of family planning grew substantially in Year 1 (12,691) and Year 2 (19,485) across all Christian Health Associations as compared to the baseline year (3,551). Cumulatively, 32,176 clients took up a method during the intervention, and 43 percent of clients received this service at the community level. According to a provider competency checklist, facility- and community-based providers were able to adequately counsel clients on new fertility awareness methods. Integration of Christian Health Associations into the national family planning strategy improved through participation in routine technical working group meetings, and the Ministries of Health in Rwanda and Uganda recognized them as credible family planning partners. Findings suggest that by strengthening capacity using a systems approach, Christian Health Associations can meaningfully contribute to national and international family planning goals. Increased attention to community-based family planning provision and to mainstreaming family planning service delivery across Christian Health Associations is recommended.